2012
DOI: 10.1590/s1516-89132012000600004
|View full text |Cite
|
Sign up to set email alerts
|

New protein sources in adults diet for mass-rearing of Anastrepha fraterculus (Diptera:Tephritidae)

Abstract: The aim of this study was to find alternatives to reduce the cost of mass production of the South American fruit fly (A. fraterculus) by looking for locally available products as protein source in the diet of adults to replace the imported product without changing the quality parameters. Two yeast from a Brazilian company were evaluated.The quality parameters showed that the imported hydrolyzed yeast used in the adult diet could be perfectly replaced by the local products tested, with a reduction of over 80% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
(9 reference statements)
1
9
0
2
Order By: Relevance
“…Média±erro-padrão dos parâmetros biológicos de Anastrepha fraterculus, criada em dieta artificial, com diferentes quantidades de ágar e bagaço seco de cana-de-açúcar, em condições de temperatura de 25±2ºC, UR de 70±10% e fotófase de 12 horas (1) . Morelli et al (2012) e Silva Neto et al (2012), os quais utilizaram fontes proteicas oriundas de produtos comerciais nacionais (Bionis), foram observados melhores resultados nos parâmetros biológicos avaliados do que os obtidos com a fonte proteica importada, com diminuição em mais de 80% no custo de produção. Assim, verifica-se que as dietas A e B à base de extrato de levedura são adequadas para a criação dos insetos adultos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Média±erro-padrão dos parâmetros biológicos de Anastrepha fraterculus, criada em dieta artificial, com diferentes quantidades de ágar e bagaço seco de cana-de-açúcar, em condições de temperatura de 25±2ºC, UR de 70±10% e fotófase de 12 horas (1) . Morelli et al (2012) e Silva Neto et al (2012), os quais utilizaram fontes proteicas oriundas de produtos comerciais nacionais (Bionis), foram observados melhores resultados nos parâmetros biológicos avaliados do que os obtidos com a fonte proteica importada, com diminuição em mais de 80% no custo de produção. Assim, verifica-se que as dietas A e B à base de extrato de levedura são adequadas para a criação dos insetos adultos.…”
Section: Resultsunclassified
“…Hansen, 1883, importada, o que eleva os custos de produção dos insetos (Aluja et al, 2001). A substituição destes ingredientes importados por produtos nacionais pode representar um avanço na criação de mosca-das-frutas, para o controle biológico e a utilização da técnica do inseto estéril (Morelli et al, 2012;Silva Neto et al, 2012).…”
Section: Introductionunclassified
“…Egg hatch is a parameter that requires improvement. The addition of raw wheat germ (Triticum aestivum L.) in adult diet and the change in the protein source from imported to local hydrolyzed yeast (Morelli et al, 2012), as well as the bubbling of eggs before seeding, increased egg hatch in the present methodology that can be improved further by more effectively preventing egg desiccation. Vera et al (2007) reported egg hatch rates above 80 % when the relative humidity in the room containing adult cages was controlled with a humidifier.…”
Section: Discussionmentioning
confidence: 99%
“…In the 26 th generation the imported yeast was replaced by a local one, Bionis YE MF® (Morelli et al, 2012;Silva Neto et al, 2012). Below the food station there was also a water supply (deionized water and sodium benzoate solution at 0.03 % to avoid fungal growth), which was closed but had a single longitudinal gap at the top through which a filter paper allowed access to water.…”
Section: Domestication Of a Fraterculus Sp1mentioning
confidence: 99%
“…Papaya fruits were provided to the flies as oviposition substrate (MACHOTA JÚNIOR et al, 2010). The diet of adults was composed of a solid diet with wheat germ, beer yeast (Bionis ® YE MF), and refined sugar at a ratio of 1:1:3 (MORELLI et al, 2012).…”
Section: Fruit Fly Rearingmentioning
confidence: 99%